2017
DOI: 10.1037/adb0000280
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate meta-analysis of motivational interviewing process and outcome.

Abstract: Motivational interviewing (MI) theory proposes a process whereby a set of therapist behaviors has direct effects on client outcomes as well as indirect effects through in-session processes such as client change talk. Despite clear empirical support for the efficacy of MI across settings, the results of studies evaluating proposed links between MI process and outcome have been less clear. In the present study, we used a series of multivariate meta-analyses to test whether there are differential relationships be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 49 publications
(110 reference statements)
8
56
0
Order By: Relevance
“…In the present study, results suggest that specific MI techniques function differently in their association with subsequent client statements about change. Specifically, open questions and complex reflections are most likely to be associated with a transition from ST to CT. Open questions are also associated with more ST after CT, which is consistent with correlational relationships reported in recent meta-analyses (Magill et al, 2014; Magill et al, 2018; Pace et al, 2017; Romano et al, 2017). Open questions can have no valence (“Tell me about your drinking”) or can explicitly solicit CT or ST (“Tell me some of the things you like about drinking” vs “What are some of the not so good things about drinking?”).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, results suggest that specific MI techniques function differently in their association with subsequent client statements about change. Specifically, open questions and complex reflections are most likely to be associated with a transition from ST to CT. Open questions are also associated with more ST after CT, which is consistent with correlational relationships reported in recent meta-analyses (Magill et al, 2014; Magill et al, 2018; Pace et al, 2017; Romano et al, 2017). Open questions can have no valence (“Tell me about your drinking”) or can explicitly solicit CT or ST (“Tell me some of the things you like about drinking” vs “What are some of the not so good things about drinking?”).…”
Section: Discussionsupporting
confidence: 90%
“…At an aggregate level, meta-analyses show more ST is associated with less behavior change, a combined measure of CT and ST is associated with more behavior change, and CT alone does not have a predictive effect (Magill et al, 2014). Another recent meta-analysis similarly found that ST was associated with worse MI outcomes, and the effect for CT was non-significant (Pace et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been hypothesised that the therapist's adherence to the MI Spirit increases the change talk from the client, which in turn is associated with positive behaviour change outcomes (Copeland et al, ; Moyers, Martin, Houck, Christopher, & Tonigan, ). A recent meta‐analysis found equivocal support for the predictive role of client change talk, however it did find that more sustain talk (i.e., when participants express their own arguments against change) was predictive of poorer outcome (Pace et al, ). In terms of client language, commitment language specifically has been found to be an important predictor of behaviour change (Amrhein, Miller, Yahne, Palmer, & Fulcher, ; Copeland et al, ).…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…Motivation can also be reduced, and therefore change or action less likely, when a range of personal beliefs or concerns argue against change (Pace et al, ). In terms of compassionate action, several fears, resistances and blocks have been identified (Gilbert et al, ).…”
mentioning
confidence: 99%
“…However, the state of the art in the area of valid analysis of sequential counselor-client utterances has only recently advanced to a point where it appeared worthwhile to analyze utterance transitions in the small sample of inpatients who participated in our original study. As data accumulate on the mechanisms and processes of MI conversations, the complexity of interacting factors is the focus of an ongoing discourse (Pace et al 2017), to which this study is an additional contribution from a care context where knowledge about MI mechanisms has not yet been charted.…”
mentioning
confidence: 99%